Pelatihan Pembuatan Jajanan Berupa Olahan Bahan Dasar Kelor bagi Masyarakat untuk Meningkatkan Status Gizi Anak Prasekolah di Desa Botumoito - Radia Hafid; Ridha Hafid; Fatmawaty Damiti; Ratna Ahmad (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Nutritional problems in preschool children in Indonesia, including in Botumoito Village, Botumoito Sub-district, Boalemo District, are a major concern in an effort to improve the quality of public health. One of the solutions offered is the utilisation of Moringa (Moringa oleifera), which is rich in nutrients such as vitamins, minerals and protein. This training activity aims to improve the knowledge and skills of the community, especially mothers, in processing moringa into healthy snacks for preschool children. The training method includes an understanding of the nutritional content of moringa, moringa-based food processing techniques, as well as how to present it attractively to children. The results of this training are expected to improve the nutritional status of preschool children through better quality food intake and open economic opportunities for the community through the production and sale of moringa-based snacks. The programme is also expected to have a sustainable positive impact on improving family welfare and children's health in the area.